L-shaped association between dietary iron intake and HPV infection: a cross-sectional analysis based on national health and nutrition examination survey 2005–2016 - Chen, Xiaotong; Chen, Haiwei; Chen, Yuling; Tang, Lixin; Liu, Jiaqi; Ou, Yu-Hua (Frontiers in Nutrition, 2025)
BackgroundHuman Papillomavirus (HPV) infection is a ubiquitous sexually transmitted infection globally, frequently associated with sexual behaviors characterized by increased frequency and multiple partnerships. The relationship between varying levels of dietary iron intake and the occurrence of Human Papillomavirus (HPV) infection remains an unresolved question in the scientific community. The objective of our study was to investigate the potential relationship between the consumption of dietary iron and HPV infection.MethodsOur investigation drew upon comprehensive datasets from 7,819 participants enrolled in the National Health and Nutrition Examination Survey (NHANES) from 2005 to 2016. Employing a cross-sectional analytical framework, we delved into the potential correlation between dietary iron consumption and Human Papillomavirus infection. To statistically assess this relationship, we utilized weighted multivariate logistic regression models. Additionally, we implemented smooth curve fitting and threshold effect analysis, to delineate the complex, nonlinear association between iron intake and HPV infection. Furthermore, we conducted subgroup analyses.ResultsAfter adjusting for multiple confounding variables, our results demonstrated a statistically significant inverse association between iron intake and HPV infection (OR = 0.988, 95% CI: 0.979–0.998, p = 0.018). It’s worth noting that, in comparison to individuals in the quartile with the lowest iron intake, those in the highest quartile exhibited a 23.2% reduction in the odds of HPV infection for each incremental unit of iron intake (OR = 0.768, 95% CI: 0.634 to 0.930, p = 0.009). A refined analysis employing smoothing curve fitting techniques unveiled an L-shaped correlation, delineating a specific relationship between dietary iron intake and the incidence rate of Human Papillomavirus infection. When iron intake was <16.99 mg, a higher incidence of HPV infection was associated with lower levels of iron intake. (OR = 0.968, 95% CI: 0.956–0.980, p < 0.001).ConclusionThe presence of an L-shaped association between iron intake and HPV infection underscores and emphasizes the possible beneficial effect of sufficient iron intake in reducing the likelihood of HPV infection.